Abridged Science for High School Students : the Nuclear Research Foundation School Certificate Integrated. - Messel, H. (Elsevier Science, 2014)
Abridged Science for High School Students, Volume I is a general science book that provides a concise discussion of wide array of scientific topics. The book is designed to supplement integrated science courses. The contents of the text cover a wide variety of scientific disciplines and are not structured in any way. The coverage of the book includes discussions on matter, heat, weather, gravity, time, and evolution. The book will be of great interest to anyone who wants to have access to a wide variety of scientific disciplines in one publication.